Study of lipid levels in diabetes mellitus with special reference to diabetic retinopathy - C. M., Shyam Sundar; Jearth, Vaneet (International Journal of Advances in Medicine, 2018)
Background: Diabetic retinopathy is a very common, potentially preventable, long term, microvascular complication of diabetes mellitus and leading cause of visual disability and blindness. It is considered hallmark of generalized microangiopathy occurring in diabetic patient. The present study was designed to study the lipid levels in patients of diabetes mellitus and further analyse the data with reference to occurrence of diabetic retinopathy. Methods: It was a case control study of 30 cases consisting patients with diabetic retinopathy and 30 controls with diabetes and no diabetic retinopathy. Fasting lipid profile, FBS, PPBS, HbA1C and BMI were measured in all subjects. Results: 34 males (57%) and 26 (43%) females were recruited in the study. The mean duration of diabetes was 8.5±5 yrs. The average HbA1C was 8.2±1.3 in Diabetic Retinopathy (DR) group and 7.5±0.9 in patients with no Diabetic Retinopathy (NDR). 21 (70%) patients in DR group had dyslipidaemia, whereas 13 (43.3%) patients in NDR had dyslipidaemia, average cholesterol was 188.30±46.48 mg/dl in patients with DR, 182.50±34.74 mg/dl in patients without DR. Conclusions: Dyslipidaemia was found to be more common in patients having Diabetic Retinopathy than in those without DR and the association was statistically significant. Mean cholesterol levels were found to be higher in cases and mean HDL level was found to be higher in controls but the relationship was not found to be statistically significant. No association was found between other lipid fractions and retinopathy.